Neuroimaging identifies increased manganese deposition in infants receiving parenteral nutrition,. Issue 6 (11th November 2015) - Aschner, Judy L; Anderson, Adam; Slaughter, James Christopher; Aschner, Michael; Steele, Steven; Beller, Amy; Mouvery, Amanda; Furlong, Heather M; Maitre, Nathalie L
ABSTRACT: Background: Manganese, an essential metal for normal growth and development, is neurotoxic on excessive exposure. Standard trace element–supplemented neonatal parenteral nutrition (PN) has a high manganese content and bypasses normal gastrointestinal absorptive control mechanisms, which places infants at risk of manganese neurotoxicity. Magnetic resonance (MR) relaxometry demonstrating short T1 relaxation time (T1R) in the basal ganglia reflects excessive brain manganese accumulation. Objective: This study tested the hypothesis that infants with greater parenteral manganese exposure have higher brain manganese accumulation, as measured by MR imaging, than do infants with lower parenteral manganese exposure. Design: Infants exposed to parenteral manganese were enrolled in a prospective cohort study. Infants classified as having high manganese exposure received >75% of their nutrition in the preceding 4 wk as PN. All others were classified as having low exposure. Daily parenteral and enteral manganese intakes were calculated. Whole-blood manganese was measured by high-resolution inductively coupled plasma mass spectrometry. Brain MR relaxometry was interpreted by a masked reviewer. Linear regression models, adjusted for gestational age (GA) at birth, estimated the association of relaxometry indexes with total and parenteral manganese exposures. Results: Seventy-three infants were enrolled. High-quality MR images were available for 58 infants, 39 with high and 19 with low manganese exposure. Four infants with a high exposure had blood manganese concentrations >30 µg/L. After controlling for GA, higher parenteral and total manganese intakes were associated with a lower T1R ( P = 0.01) in the globus pallidus and putamen but were not associated with whole-blood manganese (range: 3.6–56.6 µg/L). Elevated conjugated bilirubin magnified the association between parenteral manganese and decreasing T1R. Conclusion: A short T1R for GA identifies infants at risk of increased brain manganese deposition associated with PN solutions commonly used to nourish critically ill infants. These trials were registered at clinicaltrials.gov as NCT00392977 and NCT00392730.